Developing countries in international trade relations - Satish Kumar, 1952- (Allahabad : Chugh Pub., 1987)
Study with reference to India
Originally presented as the author's thesis (Ph. D.--Kanpur University)
Includes bibliographical references
Keywords: Terms of trade -- India; Terms of trade -- Developing countries